Problematika Pembelajaran Jarak Jauh Mata Pelajaran Bahasa Daerah (Jawa) Di Masa Pandemi Covid 19 - Utami, Sri; Wardani, Dimas Singgih Sulistyo (Jurnal Likhitaprajna, 2021)
Javanese language subjects are based on a cultural framework that includes three forms of culture, starting from what appears on the surface in the form of physical culture, then social systems, to the system of ideas that exist in Javanese culture. In this case, the Javanese language functions as a means of communication as well as of preserving and developing Javanese cultural values. Thus the learning approach is more directed to a communicative and pragmatic approach by emphasizing the affective aspect. Unggah-ungguh basa is a manifestation of the Javanese cultural value system as a form of excellence in the Javanese language. This is a point of emphasis so that anyone who learns Javanese is expected to be able to speak Javanese skillfully, behave politely, and have good character. The current problem, with the pandemic, is that most of the learning is carried out remotely. Of course, in the implementation of distance learning, there are many problems or obstacles that must be accepted. Basically distance learning is a type of learning where students are far from the educator, so that education cannot be done face-to-face and the delivery of messages from educators to students must be done through the media. Distance learning during the pandemic is an alternative to teaching and learning activities that are usually carried out offline. Utilizing technology that is always evolving in the world of education. For this reason, the aspects studied both pragmatically and theoretically in this study are the problems in the implementation of distance learning of Javanese language, namely the readiness of teachers and students, the obstacles faced when distance learning takes place in schools.